Improving Students’ Writing Skills in Composing Descriptive Texts with Clustering Technique: A Lesson Learned from Vocational Schools - Jamaluddin; Jupri; Arif Rahman; Hassan, Ahmad Javed (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study investigates the use of clustering techniques to improve students' writing skills in composing descriptive texts. This study used Classroom Action Search (CAR) as the research method. This study consisted of two cycles. Each cycle consists of four steps: Planing, Action, Observation, and Reflection. The researchers conducted this study over almost a month, as each cycle was conducted in three sessions. To collect and analyze the data, the study used information from interviews, observations, questionnaires, and students' pre-test and post-test performance to corroborate the data collected. The results of this study indicate that using clustering techniques in teaching descriptive writing can improve students' writing skills. The students' responses showed that they were interested in learning the subject of writing because they found it easy to write using this technique. Additionally, students' ability on pre-test and post-test showed significant improvement. Therefore, the average value for pre-test was 37.30. In the first cycle, the average was 71.60. On the other hand, the average for the second cycle was 80.45. This means that there was an average improvement of 34.30 points or 91.96% from the student's score from pre-study to the first cycle, and an improvement of 43.14 points or 115.66% in the average score compared to the student's score from pre-study to the second cycle. Based on the this result, the study concluded that teaching descriptive English writing to the 10th grade of SMKN 3 Mataram students using clustering techniques can improve their writing ability.